2012
DOI: 10.1007/s10705-012-9542-9
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic dinitrogen fixation by trees: an underestimated resource in agroforestry systems?

Abstract: We compiled quantitative estimates on symbiotic N2 fixation by trees in agroforestry systems (AFS) in order to evaluate the critical environmental and management factors that affect the benefit from N2 fixation to system N economy. The so-called ''N2-fixing tree'' is a tripartite symbiotic system composed of the plant, N2-fixing bacteria, and mycorrhizae-forming fungi. Almost 100 recognised rhizobial species associated with legumes do not form an evolutionary homologous clade and are functionally diverse. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 226 publications
1
48
0
3
Order By: Relevance
“…These values are much higher than the global estimates (23-176 kg N ha −1 year −1 ) for food legumes and herbaceous pasture and fodder legumes (Herridge et al, 2008). Among the nonlegume−Frankia associations, N-fixation has been estimated at 40-320 kg N ha −1 year −1 for alder (Russo, 2005) and casuarina 73 kg N ha −1 year −1 (Nygren et al, 2012). Although the annual N inputs vary widely between species and even among provenances of the same species across different locations and stand age, the amounts reported are enough to fulfill crop N needs for sustained yield (Nygren et al, 2012).…”
Section: Improvement In Soil Nutrient Cyclingmentioning
confidence: 81%
See 3 more Smart Citations
“…These values are much higher than the global estimates (23-176 kg N ha −1 year −1 ) for food legumes and herbaceous pasture and fodder legumes (Herridge et al, 2008). Among the nonlegume−Frankia associations, N-fixation has been estimated at 40-320 kg N ha −1 year −1 for alder (Russo, 2005) and casuarina 73 kg N ha −1 year −1 (Nygren et al, 2012). Although the annual N inputs vary widely between species and even among provenances of the same species across different locations and stand age, the amounts reported are enough to fulfill crop N needs for sustained yield (Nygren et al, 2012).…”
Section: Improvement In Soil Nutrient Cyclingmentioning
confidence: 81%
“…N availability and uptake The percentage of N derived from the atmosphere (NDFA) is more than 59% according to a recent analysis of 38 cases using N isotopic analyses (Nygren et al, 2012). Under humid and sub-humid conditions, on average NDFA was 69% in Table 2 Vegetable yield a response to biomass transfer using fertilizer tree prunings from sub-Saharan Africa young trees and 63% in periodically pruned trees compared to 54% in free-growing (nonpruned) trees (Nygren et al, 2012).…”
Section: Improvement In Soil Nutrient Cyclingmentioning
confidence: 99%
See 2 more Smart Citations
“…Results of Douxchamps et al (2011) revealed that most of the amendment N remained in the soil for maize cultivation under in-corporation of canavalia residues which allowed N recovery of 12% [26]. Nygren et al (2012) reported that leaf litter and green mulch applications release N slowly to the soil and mostly benefit the crop through long-term soil improvement [27]. In this way, Ambrosano et al (2013) suggested that legume residue decomposition provided long-term supply of N for the subsequent crops, by not supplying the nutrient as an immediate source [28].…”
Section: Maize Cropping and N Uptakementioning
confidence: 99%